A formação continuada de professores do Pacto em escolas públicas estaduais abrangidas pela 24ª CRE - Giacomini, Alexandre (2017)
This work investigates the topic of the continuous formation of teachers, which was developed aiming the course of continuous formation, pertaining to the National Pact for the Support of High School (Pacto), offered for educators of the state schools of Brazil. In this research, we analyzed the project in five state funded schools in the central region of RS, belonging to the 24th Regional Coordination of Education (CRE), during 2014 and 2015. The general objective of this study is to analyze advances and difficulties that occurred during and after the process of continuous formation of Pacto teachers in these schools and the specific objectives are to verify which opinions the teachers have about the teaching knowledge put into action in the school context; to investigate if there is a correlation between the teaching knowledge “continuous formation of Pacto” and the other kinds of knowledge which are developed in these schools; to analyze which opinions the teachers and study advisors have about the topics that appeared in Pacto in the school context and to identify and describe the interdisciplinary activities that were developed and implemented during and after the Pacto in these schools. Concerning methodological aspects, this is a mixed research, one that includes elements of qualitative methods (field study) and quantitative (opinion and correlation survey). The data collection, in the quantitative part, occurred by means of a 5-point Likert scale questionnaire; the qualitative part was done with the following instruments: direct individual non participating observation recorded on the logbook, document analysis, questionnaire and semi structured interview. The total of researched subjects was 74 teachers and 5 study advisors that work in the high school of the five schools aforementioned. The analysis of the data used in the quantitative part was the statistic analysis and in the qualitative part was the discursive textual analysis. The results of the opinion survey (quantitative) point to the predominance of teachers’ favorable opinions towards the eight blocks of teaching knowledge that were analyzed; concerning the correlation research (also quantitative), the results showed moderate and strong correlation between the teaching knowledge block of the “Pacto continuous formation” with the block “professional activity” and the block “use of scientific pedagogical practices on a daily basis”, respectively. From the qualitative analysis, 12 categories emerged: the Pact program in the view of educators; the activities/methodologies developed during the two stages of Pacto; the authors and the language used by the Pacto notebooks; professional (de)valuation; the role of the study advisor and their formation; the expectances of Pacto; participation and continuity of the youngsters in school; participation of teachers in the school democratic management; interdisciplinarity: it is still difficult, however, conjunct construction is aimed; curriculum: old problems, new perspectives; interdisciplinary activities implemented; and the learning evaluation: possibility of integration. It was concluded that the continuous formation in service in the school locus may contribute for a group of actions concerning the teachers’ formation and, consequently, for an improvement of teaching quality. Thus, it is of the utmost importance that the public policies of educational scope and the researchers of the area encourage the promotion of the processes of continuous formation of teachers.